(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, a 9-month curriculum has been developed for students in the first and second academic years of the extended day of sports schools with the orientation of young volleyball players to a modern sports specialty. The main part of the developed exercises is aimed at fostering physical qualities, teaching the elements of volleyball, as well as teaching exercises of other sports.